If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2 = 6 Reorder the terms: -2 + 4x = 6 Solving -2 + 4x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4x = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 4x = 6 + 2 4x = 6 + 2 Combine like terms: 6 + 2 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| -16y=0 | | 3(m-9)= | | 3x(x-12)=0 | | (x^2-x+.25)=(.3+x) | | 8-4(m+5)= | | X+2=3x+2-2x | | a^4-12a^2+35=0 | | 6a(2a-1)-(3a^2-3a)= | | -8x=4 | | n-15=30 | | -30-5m=-4(m+7) | | 8x^2-11x+3=0 | | 27=17-2y | | -2=2x+10 | | 26+4a=6a | | 35x^2+56x+21=0 | | 4s=76 | | 10x-3(x-6)=11+30 | | x^2+y^2-2x+14y+14=0 | | C=0.4t+1 | | 3(x+2)-5=10x-3 | | q-11=74 | | 2x-15=x+30 | | -2(r+7)=r+1 | | A=(3Y+1)*27 | | ln(9x-1)=2 | | 17=-2x+7 | | C=0.4(t-10)+5 | | 2x+5=11-4x | | 135x^2+60x+5=0 | | 0=-2.91x-30.58 | | 3f-7=63-2f |